BROMATOLOGICAL ANALYSIS OF GUANDU BEAN CULTIVATED IN RED WATERFOOD IN THE SEMI-ARID FOR FORAGE PRODUCTION - Dantas, Silvia Maria; Rodrigues, Vicente de Paulo; Neves, Romildo da Silva; Barbosa, Rafaela Ribeiro; Matsunaga, Wendy Kaori (Revista Brasileira de Engenharia de Biossistemas, 2021)
In the semiarid region, mitigation policies to fight droughts have been implemented. Protein banks are one of the strategies used to secure the supply of food for animals, where native or adapted forage plants are cultivated. Pigeon pea (Cajanus cajan (L.) Mills) is one of the legumes used in animal feed through forage production, with characteristics of adaptation to the climatic conditions of the Semiarid region. The research was carried out at the Experimental Agrometeorological Station-EstAgr/DCA, located in the city of Campina Grande-PB. The objective of this research was to carry out chemical analysis of dry matter (DM) and mineral analysis for pigeon pea of ​​the biocolor DC variety, being cultivated in a rainfed system distributed in three plots using treatments T1 (1.0 m x 0.50 m), T2(1.0 m x 1.0 m) and T3(1.5 m x 1.5 m). The design was completely randomized, measuring the mean for the variables. The results demonstrated the forage potential for animal feed of pigeon pea cultivated in protein banks in the semiarid region under rainfed condition.